Single dose testosterone administration modulates emotional reactivity and counterfactual choice in healthy males. (April 2018) - Wu, Yin; Clark, Luke; Zilioli, Samuele; Eisenegger, Christoph; Gillan, Claire M.; Deng, Huihua; Li, Hong
Highlights: We investigated effects of testosterone in males on emotional reactivity and counterfactual choice. Testosterone increased emotional reactivity to obtained and counterfactual outcomes. Testosterone increased the ability to use anticipated regret in guiding choice. Testosterone reduced choice based on expected value. Abstract: Testosterone has been implicated in the regulation of emotional responses and risky decision-making. However, the causal effect of testosterone upon emotional decision-making, especially in non-social settings, is still unclear. The present study investigated the role of testosterone in counterfactual thinking: regret is an intense negative emotion that arises from comparison of an obtained outcome from a decision against a better, non-obtained (i.e. counterfactual) alternative. Healthy male participants (n = 64) received a single-dose of 150 mg testosterone Androgel in a double-blind, placebo-controlled, between-participants design. At 180 min post-administration, participants performed the counterfactual thinking task. We applied a computational model derived from behavioral economic principles to uncover latent decision-making mechanisms that may be invisible in simple choice analyses. Our data showed that testosterone increased the ability to use anticipated regret to guide choice behavior, while reducing choice based on expected value. On affective ratings, testosterone increased sensitivity to both obtained and counterfactual outcomes. These findings provide evidence that testosterone causally modulates emotional decision-making, and highlight the role of testosterone in affective sensitivity.